2000
DOI: 10.2214/ajr.174.6.1741551
|View full text |Cite
|
Sign up to set email alerts
|

Comparing MR Imaging and CT in the Staging of Gastric Carcinoma

Abstract: MR imaging was comparable to helical CT in the T and N staging of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
1
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(105 citation statements)
references
References 11 publications
2
95
1
7
Order By: Relevance
“…The reported accuracy rate is approximately 51%-59% (Dux et al 1999;Sohn et al 2000), and the staging of early gastric cancer is far from satisfactory. Newly developed PET-CT technology using computer software can fuse the PET metabolic-change image with the 3D image of the corresponding anatomical location in the CT image, thus achieving both qualitative and positioning diagnosis in one examination (Townsend and Beyer 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The reported accuracy rate is approximately 51%-59% (Dux et al 1999;Sohn et al 2000), and the staging of early gastric cancer is far from satisfactory. Newly developed PET-CT technology using computer software can fuse the PET metabolic-change image with the 3D image of the corresponding anatomical location in the CT image, thus achieving both qualitative and positioning diagnosis in one examination (Townsend and Beyer 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In the evaluation of regional lymph nodes in gastric cancer, various imaging modalities, such as computed tomography (CT), endoscopic ultrasonography (EUS), and conventional magnetic resonance imaging (MRI) have been used, with lymph nodes assessed according to size or morphologic criteria. The reported accuracy of CT, EUS, and conventional MRI for the N-staging of gastric cancer was 43%-80%, 65%-87%, and 34%-65%, respectively, and this level of diagnostic perfor- mance was not suffi cient for making a decision among treatment strategies for gastric cancer [4][5][6][7][8][9][10][11][12][13]. Recently, a lymphographic contrast medium of iron-containing nanoparticles, referred to as ultrasmall superparamagnetic iron oxide (USPIO), has received attention in the evaluation of lymph nodes in various types of malignancy, such as neck, prostatic, rectal esophageal, breast, and gastric cancers [14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, precise lymph-node staging greatly infl uences the decision on the mode of treatment. For the evaluation of regional lymph nodes in gastric cancer, the nodes have generally been defi ned according to size or morphologic criteria in several imaging modalities, such as computed tomography (CT), endoscopic ultrasonography (EUS), and conventional magnetic resonance imaging (MRI), but these methods have not been confi rmed as suffi ciently effective [4][5][6][7][8][9][10][11][12][13]. Recently, the use of ultrasmall superparamagnetic iron oxide (USPIO), which is a lympho-graphic contrast medium for MR imaging, has been of interest in the evaluation of lymph nodes in patients with neck, prostatic, rectal, esophageal, breast, and gastric cancers [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, while the pre-operative T staging ability of MRI is highly accurate, a publication bias may be present, as all 3 studies reported excellent results (compared to the literature found on CT scans which included publication of poor results), which may have caused an overestimation of its performance abilities. Furthermore, current MRI protocols are breath-hold-dependent [12,13,36,49,51]; as such, it is possible that the patient cohorts included in these studies were better able to comply than the gastric cancer population as a whole.…”
Section: Evaluation Of T Stagingmentioning
confidence: 99%